IMPLEMENTASI SISTEM INFORMASI PRESENSI SISWA DENGAN QR CODE BERBASIS WEB MENGGUNAKAN METODE V-MODEL (STUDI KASUS :SMKN 7 KABUPATEN TANGERANG) - Abdul Gani Fattah; Samso Supriyatna (Journal of Research and Publication Innovation, 2026)
In the world of education, efficient administrative processes are very important to support the smooth running of teaching and learning activities. One aspect of administration that often requires special attention is recording student attendance. At SMKN 7 Tangerang Regency, recording student attendance is still carried out using attendance agenda books, namely through physical recording which is prone to causing data inaccuracies and takes quite a long time. This condition hampers efficiency in the process of processing student attendance data which should be done more quickly and accurately. This research aims to overcome problems in the student attendance process which is still carried out using the attendance agenda book at SMKN 7 Tangerang Regency. The scope of the research includes the development of a web-based student attendance information system using QR Code as a media for identifying attendance. This system is designed to be accessed by teachers and students, so that the attendance process can be carried out digitally and in real-time. The system development method used is the V-Model. The final results of the research show that the implementation of a QR Code-based attendance information system increases efficiency, reduces the potential for fraud, speeds up data validation, and makes recaps, reports and evaluations of student discipline easier.